Penerapan Tax Planning Atas Pajak Penghasilan Badan Pada CV. Pemuda Mandiri Food - Sudirman abdi; Maryam Maryam (Fakultas Ekonomi Universitas Indonesia Timur, 2021)
This study aims to determine the increase in the efficiency of earnings management in CV. Pemuda Mandiri Food (CV.PMD) by implementing tax planning as an effort to improve earnings management. The type of research used is descriptive qualitative with the use of secondary data, namely financial statements for 2019 and 2020 with a comparative method, namely comparing the company's earnings management before and after the implementation of tax planning. The results show that with the existence of tax planning and systematic financial statement preparation, CV .PMD can increase the company's revenue and achieve the expected target. This tax planning company can improve the efficiency of earnings management and minimize the amount of the company's tax burden which in turn can improve earnings management and company income. By implementing tax planning there are tax savings that occur in the company.